The roles of gaze and head orientation in face categorization during rapid serial visual presentation - Or, Charles C.-F. (2022)
Little is known about how perceived gaze direction and head orientation may influence human categorization of visual stimuli as faces. To address this question, a sequence of unsegmented natural images, each containing a random face or a non-face object, was presented in rapid succession (stimulus duration: 91.7 ms per image) during which human observers were instructed to respond immediately to every face presentation. Faces differed in gaze and head orientation in 7 combinations - full-front views with perceived gaze (1) directed to the observer, (2) averted to the left, or (3) averted to the right, left ¾ side views with (4) direct gaze or (5) averted gaze, and right ¾ side views with (6) direct gaze or (7) averted gaze - were presented randomly throughout the sequence. We found highly accurate and rapid behavioural responses to all kinds of faces. Crucially, both perceived gaze direction and head orientation had comparable, non-interactive effects on response times, where direct gaze was responded faster than averted gaze by 48 ms and full-front view faster than ¾ side view also by 48 ms on average. Presentations of full-front faces with direct gaze led to an additive speed advantage of 96 ms to ¾ faces with averted gaze. The results reveal that the effects of perceived gaze direction and head orientation on the speed of face categorization probably depend on the degree of social relevance of the face to the viewer.